Performance criteria and assessment of vendors in government sponsored entrepreneur development programme - Yahya, Salleh; Kingsman, Brian G. (Academy of Marketing Science, 1997)
In Entrepreneur Development Programme, vendor rating is important not only in supplier selection and in deciding how to allocate business but also determine where scare development effort is best-applied. The paper reviews current methods for vendor rating and finds them wanting. It illustrates a new approach based on the use of Saaty’s Analytic Hierarchy process method, which was developed to assist in multi-criteria decision problems. The new method overcomes the difficulties associated with the categorical and simple linear weighted criteria ranking methods. It provides a more systematic way of deriving the weights to he used and for scoring the performance of vendors.